Interplay between the tiers in Croatian local government : who is winning the interdependence game - Škarica, Mihovil (Array, 2020)
The paper examines, analyses, and evaluates the relations between the first and second tiers of the Croatian local government system and their longitudinal and cross-sectoral dynamics. Membership in the European Union has opened new relevant horizons for national territorial governance, primarily through the advocacy of multi-level cooperative governance arrangements and by providing opportunities for the acquisition of additional resources through European structural and investment funds. These issues are evaluated by analysing formal competence distribution between the tiers, by analysing the distribution of resources between tiers and through their cooperation in regional policy domain and service delivery. Furthermore, actors’ perceptions of their mutual relations are examined via the author’s own research and the research of other scholars. After the introductory chapter, the second chapter presents a theoretical framework and context for an analysis of vertical relations within the local government system; the third chapter provides a longitudinal overview of the main features and conceptual developments of the Croatian local government system.The fourth chapter is the central part of the paper that presents and analyses the available primary and secondary data.